Measurement of CP violation parameters in B0→DK*0 decays - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2014)
An analysis of B0→DK*0 decays is presented, where D represents an admixture of D0 and ¯D0 mesons reconstructed in four separate final states: K−π+, π−K+, K+K− and π+π−. The data sample corresponds to 3.0 fb−1 of proton-proton collision, collected by the LHCb experiment. Measurements of several observables are performed, including CP asymmetries. The most precise determination is presented of rB(DK*0), the magnitude of the ratio of the amplitudes of the decay B0→DK+π− with a b→u or a b→c transition, in a Kπ mass region of ±50 MeV/c2 around the K∗(892) mass and for an absolute value of the cosine of the K*0 helicity angle larger than 0.4.
*LHCb Collaboration: R. Aaij, S. Bachmann, A. Bien, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Färber, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, M. Neuner, T. Nikodem, P. Seyfert, M. Stahl, S. Stahl, U. Uwer, M. Vesterinen, S. Wandernoth, D. Wiedner, A. Zhelelov [und 672 weitere Personen]
Im Titel ist die Zahl 0 und das Zeichen * hochgestellt
Gesehen am 05.10.2020